P1-S1.09 Trends in the aetiology of sexually transmitted infections and HIV Coinfections among STI patients attending Alexandra Health Centre, Johannesburg, South Africa (2007–2010). (10th July 2011) - Lewis, D; Ricketts, C; Bhojraj, N; de Gita, G; Magooa, P; Venter, I; Mshibe, L; Vezi, A; Muller, E; Radebe, F
Abstract : Objectives: To determine trends in the relative prevalence of aetiologies of urethral discharge (UDS), vaginal discharge (VDS) and genital ulcer (GUS) syndromes, and in the seroprevalence of syphilis, HSV-2 and HIV. Methods: Consecutive male (UDS/GUS) and female (VDS/GUS) patients were enrolled at Alexandra Health Centre, Johannesburg from January to April each year during 2007–2010. Urethral swabs (UDS), endocervical swabs/vaginal smears (VDS), genital ulcer swabs/smears (GUS) and sera (all) were collected with written informed consent. Real-time PCR assays were used to detect Neisseria gonorrhoeae (NG), Chlamydia trachomatis (CT), Trichomonas vaginalis (TV) and Mycoplasma genitalium (MG) from UDS/VDS swabs, and herpes simplex virus (HSV), Treponema pallidum (TP) Haemophilus ducreyi (HD) and Chlamydia trachomatis L1-3 (LGV) from ulcer swabs. Slides were stained for bacterial vaginosis/candidiasis (BV/CA, VDS) and granuloma inguinale (GI, GUS). Sera were tested for syphilis (rapid plasmin reagin, RPR; Omega Diagnostics), for HSV-2 (HerpeSelect IgG; Focus Diagnostics) and for HIV (Determine; Abbott Laboratories). χ 2 for linear trend analyses were undertaken with summary data (Prism v.2, GraphPad Software). Results: 928 UDS, 805 VDS and 455 GUS patients were recruited overall. Trends in the relative prevalence of most syndrome aetiologies were non-significant between 2007 and 2011—NG (UDS, 71%–79%; VDS 11%–17%), CT (UDS, 20%–25%; VDS, 27%–37%), MG (UDS, 10%–13%; VDS, 11%–14%), BV (VDS, 30%–36%), CA (VDS, 26%–31%), HSV (GUS, 53%–75%), TP (GUS, 4%–7%), HD (GUS, 0%–2%), LGV (0%–2%). There were no cases of GI. There was, however, significant decreasing trends for TV detection among UDS (4%–13%, p=0.003) and VDS (19%–34%, p=0.001) patients. Serologically, VDS patients had a decreasing trend in RPR seropositivity (1–8%, p<0.001) and, importantly, HIV coinfections decreased among both UDS (29%–39%, p=0.011) and GUS (60%–75%, p=0.032) patients. Non-significant variations in seropositivity were observed for RPR tests among UDS (1%–3%) and GUS (4%–11%) patients, for HSV-2 among all groups (UDS, 50%–60%; VDS, 74%–84%; GUS, 81%–87%), and for HIV among VDS (48%–59%) patients. Conclusions: These data suggest significant decreases in the prevalence of HIV coinfection in UDS/GUS patients and of trichomoniasis as a cause of UDS/VDS. Though the HIV trends are encouraging for men, the lack of a similar trend for women with VDS is of public health concern.